The effects of endotracheal intubation and laryngeal mask airway on the risk of myocardial ischemia in cardiac patients - (:unkn) unknown (My University, 2000)
Objective: The aim of this study was to compare the effects of endotracheal intubation and laryngeal mask airway (LMA) insertion on the risk of myocardial ischemia in patients with coronary artery disease (CAD) and/or congestive heart failure (CHF). Methods: Thirty patients, ASA III-IV, having CAD and/or CHF, undergoing elective peripheral surgery (orthopaedic, urologic, ear-nose and throat and ophthalmologic surgery) were investigated. Anesthesia was induced with 0.2 mg/kg etomidate, 15 μg/kg alfentanil and 0.1 mg/kg vecuronium i.v. in all patients. In group I the patients were intubated, in group II LMA was inserted for maintenance of airway. Mean arterial pressure (MAP), heart rate (HR), rate pressure product (RPP), and ST segmet changes were recorded. Postoperatively 12 lead electrocardiography and CPK, CPK-MB levels were also recorded. Results: MAP and RPP increased significantly 1 min after intubation in group I, there was no difference in MAP and RPP and a significant decrease in HR in group II. ST segment changes indicated ischemia were recorded 15 times in 6 patients in group I and 4 times in 3 patients in group II. Conclusion: Unless contraindicated, airway maintenance by LMA should be preferred in patients with CAD in order to protect myocardial perfusion.
Keywords: Endotracheal intubation; Laryngeal mask airway; Myocardial ischemia